2013
DOI: 10.1016/j.dental.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of the resin–dentin interface: A new approach for evaluating the durability of dentin bonds

Abstract: There are concerns regarding the longevity of resin composite restorations and the clinical relevance of in vitro bond strength testing to the durability of dentin bonds in vivo. Objective The objectives of this investigation were to: 1) develop a new method of experimental evaluation for quantifying the durability of dentin bonds, 2) apply this method to characterize the interfacial strength of a selected commercial system under both monotonic and cyclic loading, and 3) distinguish mechanisms contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 50 publications
(59 reference statements)
2
45
0
2
Order By: Relevance
“…Secondary caries are potentially facilitated by the localized high cyclic stresses at the interface and fatigue (Spencer et al, 2010; Pashley et al, 2011). Cyclic stress is detrimental to the durability of resin-dentin bonds (Mutluay et al, 2013a; 2013b). Resin composites also tend to accumulate more biofilm/plaque in the oral environment than other restoratives materials (Zalkind et al, 1998; Beyth et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary caries are potentially facilitated by the localized high cyclic stresses at the interface and fatigue (Spencer et al, 2010; Pashley et al, 2011). Cyclic stress is detrimental to the durability of resin-dentin bonds (Mutluay et al, 2013a; 2013b). Resin composites also tend to accumulate more biofilm/plaque in the oral environment than other restoratives materials (Zalkind et al, 1998; Beyth et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, as explained above, failure initiated by dentin fracture did not seem to have occurred in our fatigue tests. Compared to the results from the four-point flexure test [11], the disk in diametral compression produced lower bond strength and a slightly higher rate of reduction in fatigue life with increasing stress. These are reflected in the lower values for A and slightly higher absolute values for B in Equation (1), respectively.…”
Section: Discussionmentioning
confidence: 69%
“…Examples include micro-rotary fatigue test [13], cyclic shear and push-out tests [43], as well as cyclic four-point flexure test [11,14,44]. The present study proposed an alternative test method for assessing the fatigue resistance of the dentin-composite interface.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro laboratory studies reported decreases in dentin bond strength after long-term storage in water. Although in vivo long-term durability studies reported the degradation of hybrid layers over time, they are still limited with respect to number and adhesive type (9,10) .…”
Section: Discussionmentioning
confidence: 99%